A cell engineering strategy to enhance supercoiled plasmid DNA production for gene therapy. Issue 9 (16th March 2016) - Hassan, Sally; Keshavarz‐Moore, Eli; Ward, John
ABSTRACT: With the recent revival of the promise of plasmid DNA vectors in gene therapy, a novel synthetic biology approach was used to enhance the quantity, (yield), and quality of the plasmid DNA. Quality was measured by percentage supercoiling and supercoiling density, as well as improving segregational stability in fermentation. We examined the hypothesis that adding a Strong Gyrase binding Site (SGS) would increase DNA gyrase‐mediated plasmid supercoiling. SGS from three different replicons, (the Mu bacteriophage and two plasmids, pSC101 and pBR322) were inserted into the plasmid, pUC57. Different sizes of these variants were transformed into E. coli DH5α, and their supercoiling properties and segregational stability measured. A 36% increase in supercoiling density was found in pUC57‐SGS, but only when SGS was derived from the Mu phage and was the larger sized version of this fragment. These results were also confirmed at fermentation scale. Total percentage supercoiled monomer was maintained to 85–90%. A twofold increase in plasmid yield was also observed for pUC57‐SGS in comparison to pUC57. pUC57‐SGS displayed greater segregational stability than pUC57‐cer and pUC57, demonstrating a further potential advantage of the SGS site. These findings should augment the potential of plasmid DNA vectors in plasmid DNA manufacture. Biotechnol. Bioeng. 2016;113: 2064–2071. © 2016 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc. Abstract : The Strong Gyrase Binding Site (SGS) from three different replicons was inserted into the plasmid pUC57 and transformed into Escherichia coli DH5α. Supercoiling properties and segregational stability were measured. A 36% increase in supercoiling density was found in pUC57‐SGS, but only when SGS derived from the Mu phage and was the larger sized fragment. A twofold increase in yield was also observed for pUC57‐SGS compared to pUC57 and pUC57‐SGS displayed greater segregational stability. These findings could aid plasmid DNA manufacture.